The effect of exercise on the prevention of gestational hypertension in obese and overweight pregnant women: An updated meta-analysis - Xie, Enli; Tao, Huimin; Liu, Mengqing; Li, Changchun; Zhao, Qi (Frontiers in Public Health, 2022)
Background: Gestational hypertension (GH) is a common disease that seriously threatens the safety and health of pregnant women and their newborns. Physical exercise (PE) is widely recognized as a health maintenance method and it has numerous benefits. Studies on the association between PE and the risk of GH in obese and overweight pregnant women have generated controversial findings. This updated meta-analysis was performed to reassess the effects of PE on GH. Methods: The articles from inception to April 2022, presenting studies investigating exercise intervention and pregnancy outcomes were explored across several online databases. Heterogeneity among the included studies was estimated and tested by Q test and I2 statistic. Risk ratios (RRs) and 95% confidence intervals (CI) were calculated through either random-effect or fixed-effect models. Subgroup analyses, sensitivity analyses, and publication bias diagnoses were also conducted. Results: Twelve with 1,649 subjects were included. PE was associated with a reduced risk of GH in obese and overweight pregnant women (Pooled RR = 0.58, 95% CI =0.42-0.81, P=0.001; I2 = 24.3%). Subgroup analysis found significant trends amongst Eastern countries (RR = 0.59, 95% CI = 0.36–0.96, P =0.033). Sensitivity analysis suggested the results were stable. No publication bias was detected based on Begg’s test and Egger’s test. Conclusion: PE was associated with reduced risk of GH in obese and overweight pregnant women, especially in Eastern countries. More well-designed studies are still needed to further elaborate on these associations.